Contemporary antiplatelet therapy in acute coronary syndromes: are there differences in outcomes and discontinuation between clopidogrel and ticagrelor?. Issue 11 (5th November 2017) - Harding, Scott A.; Holley, Ana; Wilkins, Ben; Fairley, Sarah; Simmonds, Mark; Larsen, Peter D.
Abstract: Background/Aim: We studied clinical outcomes and discontinuation rates in a 'real‐world' population presenting with myocardial infarction treated with ticagrelor or clopidogrel. Methods: Between January 2012 and May 2015, 992 patients with acute myocardial infarction undergoing invasive management and adequately pre‐treated with dual antiplatelet therapy were prospectively enrolled. Platelet aggregation was measured using the Multiplate analyser. Baseline characteristics, in‐hospital outcomes and 1‐year outcomes were collected. Results: Patients treated with ticagrelor were younger and less likely to be diabetic, have a previous myocardial infarction or present with a ST‐elevation myocardial infarction (all P  < 0.05). Those treated with ticagrelor also had lower CRUSADE (Can Rapid risk stratification of Unstable angina patients Suppress ADverse outcomes with Early implementation of the ACC/AHA guidelines; 20 ± 9.4 vs 23 ± 10.1, P  < 0.0001) and GRACE (119 ± 28 vs 126 ± 32, P  = 0.002) scores. High platelet reactivity was greatly reduced with ticagrelor compared to clopidogrel (16.1% vs 37.0%, respectively; P  < 0.0001). Non‐coronary artery bypass grafting‐related thrombolysis in myocardial infarction major and minor bleeding occurred at similar rates in those treated with ticagrelor and clopidogrel. Rates of drug discontinuation in those treated with ticagrelor and clopidogrel were similar in hospital (20.2% vs 16.2%, P  = 0.18) and between discharge and 1 year (29.9% vs 27.9%, P  = 0.63). However, discontinuation due to dyspnoea, (3.3% vs 0%, P  < 0.0001) and discontinuation due to any possible drug‐related adverse event (9.3% vs 2.2%, P  = 0.0001) was more common in those treated with ticagrelor compared to clopidogrel Conclusion: Ticagrelor is paradoxically being used in lower‐risk patients rather than those most likely to benefit. Ticagrelor was associated with similar rates of bleeding but higher discontinuation rates due to adverse effects compared to clopidogrel.